Impact of North Atlantic - GIN Sea exchange on deglaciation evolution of the Atlantic Meridional Overturning Circulation - Cheng, J.; Liu, Z.; He, F.; Otto-Bliesner, B. L.; Colose, C. (Climate of the Past, 2011)
In a transient simulation of the last deglaciation with a fully coupled model (TraCE-21000), an overshoot of the Atlantic Meridional Overturning Circulation (AMOC) is simulated and proposed as a key factor for the onset of the Bolling-Allerod (BA) warming event. There is collaborating evidence for an AMOC overshoot at the BA in various proxy reconstructions although the mechanism governing its behavior is not well understood. Here, we present two new sensitivity experiments to explicitly illustrate the impact of North Atlantic - GIN Sea exchange on the AMOC's deglacial evolution. Results show that this oceanic exchange dominates the convection restarting in the GIN Sea, the occurrence of the AMOC overshoot, and the full BA warming. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000295356800016&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 Geosciences, Multidisciplinary Meteorology & Atmospheric Sciences SCI(E) 3 ARTICLE 3 935-940 7